Analisis Hasil Ujian Sekolah Berstandar Nasional di Sekolah Dasar Kecamatan Bulu pada Muatan Matematika - Latifah, Inayatul; Ardiyaningrum, Martalia; Putri, Mufida Awalia; Arifin, Ahmad Syamsul (Alma Ata University Press, 2024)
This research aims to analyze the level of difficulty of the questions and mastery of basic competencies according to the level of difficulty of the questions that have been found in the Mathematics subject in the national standard elementary school exam results in Bulu sub-district, Temanggung. This research uses a quantitative approach using descriptive methods. The population in this study is data from the USBN results in the Bulu sub-district with a sample of 35 questions answered by 613 grade 6 students, in terms of the level of difficulty the questions were classified as sufficient or medium. This can be seen from the calculation results which show that of the 30 multiple-choice questions that are classified as difficult questions, there are 4 questions (13%), 17 medium questions (57%), and 9 easy questions (30%). Meanwhile, for the 5 essay questions in the difficult category, 1 question (20%), 4 medium questions (80%), and 0 easy questions (0%).Keyword: item analysis, USBN, level of difficulty, mathematics